Transfer entropy approach for portfolio optimization: An empirical approach for CESEE markets - Tihana Škrinjarić; Derick Quintino; Paulo Ferreira (Journal of Risk and Financial Management, 2021)
In this paper, we deal with the possibility of using econophysics concepts in dynamic portfolio optimization. The main idea of the research is that combining different methodological aspects in portfolio selection can enhance portfolio performance over time. Using data on CESEE stock market indices, we model the dynamics of entropy transfers from one return series to others. In the second step, the results are utilized in simulating the portfolio strategies that take into account the previous results. Here, the main results indicate that using entropy transfers in portfolio construction and rebalancing has the potential to achieve better portfolio value over time when compared to benchmark strategies.
Keywords: 330; dynamic analysis; econophysics; portfolio selection; stock markets